Penggunaan Dompet Digital dalam Penyaluran Zakat di Indonesia - Aurora, Rif' Aida Mirza; Fauzatul Laily Nisa (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Zakat according to Islamic teachings is a solution to overcome poverty while acting as a means of distributing wealth and increasing religious awareness. In Indonesia, the development of digital wallets has made it easier to distribute zakat through applications such as DANA, LinkAja, GO-PAY, OVO, and ShopeePay. The use of digital wallets speeds up and simplifies the zakat payment process, which involves steps such as opening a verified app, accessing the zakat menu, calculating the amount to be paid, using the available payment methods, and confirming the payment to the National Amil Zakat Agency (BAZNAS). The advantages of using digital wallets in zakat payment include convenience, opportunity to donate, transaction security, clearly documented transaction records, practicality, increased awareness of religious obligations, more active participation, and increased efficiency in the zakat distribution process.